Interpretation of Legal Norms in Modern Jurisprudence: Theoretical and Practical Aspects of Human Rights Protection Under Martial Law - Sydorov, Yaroslav; Yurchenko, Vasyl; Kantor, Nataliia; Chekhovych, Tetiana; Dietochka, Anatolii (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2025)
The purpose of the research is to consider ways for the interpretation of legal norms in modern jurisprudence. Main content. It has been established that interpretation will result in a general conclusion or a sum of the findings reached by the subject of interpretation in the process of clarifying the rule of law (legal norms) using the entire set of interpretation methods, which is adequate to the actual content of this rule and meets the criteria of truth and correctness of the result of interpretation... Methodology: The methodological basis of the research is presented as comparative-legal and systematic analysis, formal-legal method, interpretation method, hermeneutic method, as well as methods of analysis and synthesis. Conclusions. It has been concluded that the procedure for achieving the goal of interpretation should be as follows: grammatical interpretation, teleological interpretation - clarification of compliance of the essence of legal norm content with the principles of law, systematic interpretation, special legal interpretation, logical interpretation, functional interpretation, historical interpretation - repeated application of the interpretation procedure when receiving new data. REFERENCES: Antoshkina, Valeriia Kostiantynivna. 2011. Reasons for the interpretation of civil law norms: Actual problems of civil law: the materials of the